2013
DOI: 10.1617/s11527-013-0072-y
|View full text |Cite
|
Sign up to set email alerts
|

Are steel fibres able to mitigate or eliminate size effect in shear?

Abstract: This paper reports some recent results of an experimental campaign on fibre reinforced concrete (FRC) beams under shear loading tested at the University of Brescia: nine full scale beams, having a height varying from 500 to 1,500 mm, were tested for investigating the effect of steel fibres on key-parameters influencing the shear response of concrete members, with special emphasis on size effect. All tested members contained no conventional shear reinforcement and different amounts of steel fibres: 0, 0.64 or 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(46 citation statements)
references
References 5 publications
3
34
0
4
Order By: Relevance
“…In fact, δu,SFRC/δu,SC increased when fibers were added to the concrete. Fiber capacity, when dosed adequately, modified the failure mode from shear to flexure, corroborating conclusions by You et al (2010), Minelli et al (2014) and Tahenni et al (2016). Therefore, V-δ showed that SFRC beams (V0.5, V0.8 and V1.0) had a predominantly ductile behavior, where the control beam, V0, revealed a fragile behavior.…”
Section: Load-displacement Relationshipssupporting
confidence: 76%
“…In fact, δu,SFRC/δu,SC increased when fibers were added to the concrete. Fiber capacity, when dosed adequately, modified the failure mode from shear to flexure, corroborating conclusions by You et al (2010), Minelli et al (2014) and Tahenni et al (2016). Therefore, V-δ showed that SFRC beams (V0.5, V0.8 and V1.0) had a predominantly ductile behavior, where the control beam, V0, revealed a fragile behavior.…”
Section: Load-displacement Relationshipssupporting
confidence: 76%
“…Therefore, a degree of crack redistribution may be established by allowing a progressive shear crack growth up to failure, with an increase in bearing capacity and ductility. For the same load level, FRC elements show a more distributed crack pattern with more closely spaced and smaller cracks [7]. On the other hand, shear crack width evolution was analyzed during the test (Fig.…”
Section: Cracking Patterns and Load-crack Width Responsesmentioning
confidence: 99%
“…SFRC makes it possible to obtain a more widely distributed cracking pattern, with smaller crack widths and less separation between cracks [4,6]. Fibers could even avoid the formation of a single critical shear crack and delay the occurrence of the shear failure mechanism [7], enhancing bearing capacity, mitigating the size effect in shear or guaranteeing the minimum shear reinforcement required by the current Codes [6]. The ability of SFRC to convert brittle concrete behavior to ductile has been extensively studied [2,5,6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Concrete shear behavior is reported as one of the most significant enhancements achieved by adding fibers to the concrete matrix [8,9]. The experimental evidences confirmed the efficiency of fibers as shear reinforcement to enhance the ultimate shear capacity and ductility of the structural elements [10,11]. The steel fibers increase the bearing capacity of the concrete elements and, therefore, bring the member up to yielding of rebars [12].…”
Section: Introductionmentioning
confidence: 97%